Gaya Bahasa Presenter MetroTV di TikTok: Analisis Wacana Kritis Model Norman Fairclough - Sanjaya, Ade Bangun; Widaswara, Rieka Yulita; Suardana, I Ketut Putu (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - The digital revolution has changed the way people consume information, including in the world of journalism. Social media such as TikTok has become a new space for mass media to deliver news. This study aims to analyze changes in journalistic communication patterns in the digital era, focusing on the language style of MetroTV Presenters on Tiktok social media. Using Norman Fairclough's Critical Discourse Analysis theory, this study analyzed four popular news videos selected through purposive sampling techniques. The results of the analysis show that the language style used is informal, humorous, and full of subtle satire. The three dimensions of Fairclough's analysis of linguistic texts, discourse practices, and socio-cultural practices show a transformation in news delivery. Presenters not only convey information, but also build closeness with young audiences through language that is relevant to popular culture and internet trends. In the digital era, the success of delivering journalistic messages depends on the media's ability to package content that is not only informative but also emotionally and socially appealing.Keywords: Critical Discourse Analysis; Style of Language; Digital Journalism; Social Media; MetroTV Abstrak - Revolusi digital telah mengubah cara masyarakat mengonsumsi informasi, termasuk dalam dunia jurnalistik. Media sosial seperti TikTok menjadi ruang baru bagi media massa dalam menyampaikan berita. Penelitian ini bertujuan untuk menganalisis perubahan pola komunikasi jurnalistik di era digital yang berfokus kepada gaya Bahasa Presenter MetroTV di media sosial Tiktok. Menggunakan teori Analisis Wacana Kritis dari Norman Fairclough, penelitian ini menganalisis empat video berita populer yang dipilih melalui teknik purposive sampling. Hasil analisis menunjukkan bahwa gaya bahasa yang digunakan bersifat informal, humoris, dan penuh sindiran halus. Ketiga dimensi analisis Fairclough teks linguistik, praktik diskursus, dan praktik sosial budaya menunjukkan adanya transformasi dalam penyampaian berita. Presenter tidak hanya menyampaikan informasi, tetapi juga membangun kedekatan dengan audiens muda melalui bahasa yang relevan dengan budaya populer dan tren internet. Dalam era digital, keberhasilan penyampaian pesan jurnalistik bergantung pada kemampuan media mengemas konten yang tidak hanya informatif tetapi juga menarik secara emosional dan sosial.Kata kunci: Analisis Wacana Kritis; Gaya Bahasa; Jurnalistik Digital; Media Sosial; MetroTV